Consumer’s Online to Impulse Buying : Consumer Traits and Situational Factors - Muzdalifah, Laily (GREENOMIKA, 2023)
OFC sales have decreased due to the covid-19 pandemic and continuing efforts to stabilize the business conditions of OFC after the covid-19 pandemic which makes it important for this research to be carried out. The research aims to determine the influence between internal (consumer traits) and external (situational factors) dimensions that influence consumers' online impulse buying. The population in this study are OFC consumers who do online impulse buying at Shopeefood. The sample in this study amounted to 100 people by taking the sampling technique, namely purposive sampling. The statistical tool used in this research is PLS 3.0. The results show that internal factors which include impulse buying tendencies, shopping enjoyment tendencies, consumer moods have a significant influence on online impulse buying, however, personal situations do not have a significant influence on impulse buying. External factors which include e-store atmosphere do not have a significant effect on impulse buying online, but Motivational activities by retailers and Product attributes have a significant influence on impulse buying.